The Whys of Social Exclusion : Insights from Behavioral Economics - Hoff, Karla; Walsh, James (Published by Oxford University Press on behalf of the World Bank, 2019)
All over the world, people are prevented from participating fully in society through mechanisms that go beyond the structural and institutional barriers that rational choice theory identifies (—poverty, exclusion by law or force, taste-based or statistical discrimination, and externalities from social networks differentiated by socioeconomic status). This paper discusses four additional mechanisms that can be explained by bounded rationality: (a) implicit discrimination, (b) self-stereotyping and self-censorship, (c) rules of thumb adapted to disadvantaged environments that are dysfunctional in more privileged settings, and (d) “adaptive preferences,” in which an excluded group comes to view its exclusion as natural. Institutions, if they are stable, come to have cognitive foundations---concepts, categories, social identities, and worldviews---through which people mediate their perceptions of themselves and the world around them. Abolishing or reforming a discriminatory institution may have little effect on the social categories it created; groups previously discriminated against by law may remain excluded through custom and habits of the mind. Recognizing new forces of social exclusion, behavioral economics identifies ways to offset them. Some interventions have had very consequential impacts.